CARA MUDAH MENYIAPKAN MATERI PEMBELAJARAN BERBASIS WEB DAN CD UNTUK BAHASA INDONESIA - Yusring Sanusi Baso (JURNAL ARBITRER, 2015)
Revolution of Information and Communication Technology (ICT) has changed the various areas of human life, including the revolution in education. Revolution of education occurs since people migrate their way of learning from conventional to digital learning, face-to-face at a certain time and place into a meeting from anywhere and anytime. In the past we used paper, now we already headed to paperless era. Several years ago, teachers and lecturers is the source of knowledge, it is the source of knowledge can be through a variety of media, such as CD-ROMs and the Internet. The way we learn is change to distant learning with free study hour. Then, it results the term e-learning, knowledge server and knowledge based society. This article discusses how to prepare simple e-learning material (web and cd-based) about Bahasa Indonesian. The program that employs to elaborate and modify the material is Hot Potatoes which is published by the University of Victoria and the Half-Baked Software. The material of Bahasa Indonesian use in this program is a set of questions on National Examination for Selection Admissions (SPMB). These questions will create an interactive multimedia material, especially web-based and CD-based material. Modules that are discussed in this article including input of data (questions, answers, etc.), output configuration (modification of the display and appearance), as well as techniques to publish on the website. In addition, it will also discuss how to keep the material in the web and CD. The final result (output) or material output from this program is the material that can be used as in learning Bahasa Indonesian, especially for self training and test. The Output will be in the form of website and CDs.